2013
DOI: 10.1016/j.celrep.2013.05.033
|View full text |Cite
|
Sign up to set email alerts
|

The Making of a Slicer: Activation of Human Argonaute-1

Abstract: Summary Argonautes are the central protein component in small RNA silencing pathways. Of the four human Argonautes (hAgo1–4) only hAgo2 is an active slicer. We determined the structure of hAgo1 bound to endogenous copurified RNAs to 1.75 Å resolution and hAgo1 loaded with let-7 miRNA to 2.1 Å. Both structures are strikingly similar to the structures of hAgo2. A conserved catalytic tetrad within the PIWI domain of hAgo2 is required for its slicing activity. Completion of the tetrad combined with a mutation on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
199
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(207 citation statements)
references
References 38 publications
6
199
1
1
Order By: Relevance
“…Structures of human AGO1 bound to endogenous co-purified RNAs or loaded with let-7 miRNA are strikingly similar to the structures of AGO2 (Faehnle et al, 2013;Nakanishi et al, 2013). Evolutionary changes that rendered hAGO1 inactive included a mutation of a catalytic tetrad residue and mutations on a loop near the actives site (Faehnle et al, 2013;Nakanishi et al, 2013).…”
Section: Human Ago1 and Ago2 Structuresmentioning
confidence: 77%
See 2 more Smart Citations
“…Structures of human AGO1 bound to endogenous co-purified RNAs or loaded with let-7 miRNA are strikingly similar to the structures of AGO2 (Faehnle et al, 2013;Nakanishi et al, 2013). Evolutionary changes that rendered hAGO1 inactive included a mutation of a catalytic tetrad residue and mutations on a loop near the actives site (Faehnle et al, 2013;Nakanishi et al, 2013).…”
Section: Human Ago1 and Ago2 Structuresmentioning
confidence: 77%
“…The core of the structural reports is thus formed by six articles reporting crystal structures of human Argonaute proteins (Elkayam et al, 2012;Schirle and MacRae, 2012;Faehnle et al, 2013;Nakanishi et al, 2013;Schirle et al, 2014;Schirle et al, 2015). Four articles describe crystal structures of AGO2 (Elkayam et al, 2012;Schirle and MacRae, 2012;Schirle et al, 2014;Schirle et al, 2015), which is capable of cleaving cognate transcripts and two describe miRNA-pathway dedicated AGO1 (Faehnle et al, 2013;Nakanishi et al, 2013).…”
Section: Ago2 Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the ability to reproducibly purify unbound hAgos [84,90] and load them with specific guides [84,90], it became apparent that this binding confers stability to not only to the guide [65,90,91,92] but also Ago itself [90]. Moreover, this binding holds the guide RNA in a conformation that is consistent in all observed structures; this is particularly evident and critical in the seed region [61].…”
Section: Hhmi Author Manuscriptmentioning
confidence: 86%
“…Recent biochemical and structural studies of hAgos have identified determinants of Argonaute slicer activity that extend beyond the active site. These are most notably in an adjacent loop to the active site and in the N domain [84][85][86][87][88]. Moreover, the activity of Agos can be modulated through post-translational modifications including proline hydroxylation that increases slicing activity, sumoylation that increases protein stability, ADP-ribosylation that relieves both slicing and translation repression, and phosphorylation that can either enhance or inhibit silencing efficacy (reviewed in [89]).…”
mentioning
confidence: 99%